2020
DOI: 10.1021/acs.jafc.0c01616
|View full text |Cite
|
Sign up to set email alerts
|

Formation of Samin Diastereomers by Acid-Catalyzed Transformation of Sesamolin with Hydrogen Peroxide

Abstract: The conversion of sesame lignans is of interest because the derived products may have potential applications. Here, in investigating the transformation of sesamin and sesamolin, main endogenous sesame lignans in sesame seeds, in both acidic aqueous and anhydrous systems, 7R,7′S-samin was identified as one of the major products of sesamolin in both systems catalyzed with common inorganic acids, but sesaminol was not generated. In investigating the effect of different oxidizing agents on the acid-catalyzed conve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…During the kinetic modeling stage, the concentrations of sesamin and asarinin were used as observables. DDAPLUS solver, included in Athena Visual Studio, integrates ordinary differential equations (ODEs) ( 10 , 11 ). This solver is a modified Newton algorithm used in conjunction with a fixed leading coefficient backward difference formula for the approximation of first-order derivatives ( 31 ).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…During the kinetic modeling stage, the concentrations of sesamin and asarinin were used as observables. DDAPLUS solver, included in Athena Visual Studio, integrates ordinary differential equations (ODEs) ( 10 , 11 ). This solver is a modified Newton algorithm used in conjunction with a fixed leading coefficient backward difference formula for the approximation of first-order derivatives ( 31 ).…”
Section: Methodsmentioning
confidence: 99%
“…Asarinin is a geometrical isomer of sesamin generated under certain conditions of temperature and acidity ( 8 ). It is formed from sesamin during refining processes (i.e., acid clay bleaching and deodorization at high temperature) ( 9 , 10 ). Compared with homogeneous catalysts (e.g., hydrochloric acid and sulfuric acid), heterogeneous catalysts such as phosphotungstic acid ( 11 ), acid cation exchange resin ( 12 ), acid clay ( 13 ), and Hβ zeolite ( 14 ) have the advantages of easier separation and recycling.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The results of a study by Nagarajan and Lee [74] have suggested that sesamolin could be a promising antileukemic agent in vivo based on its efficacy in a wehi-3B-induced leukemia model. According to Tsai et al [131] research, it has been demonstrated that the antioxidant activity of related derivatives of sesame lignans may surpass that of endogenous lignans present in sesame oil. In another research, the effectiveness of sesamolin in reducing serum and liver lipid levels, along with a simultaneous increase in liver fatty acid oxidation, was observed [132].…”
Section: Sesamolinmentioning
confidence: 99%
“…In the earlier researches, liquid mineral acids, such as HCl and H 2 SO 4 , were used as catalysts for sesamin conversion to asarinin (Kuo et al, 2011;Chen et al, 2018;Tsai et al, 2020). Nevertheless, the intrinsic catalytic activities are relatively low, and the use of these conventional mineral acids causes several problems such as environmental problems, corrosion problems, as well as difficulties of separation from products for reuse.…”
Section: Introductionmentioning
confidence: 99%